Graphdiyne material and preparation method and application thereof, lithium ion battery
By preparing graphyyne materials from bottom up, using hexazazanaphthalene structural monomer and alkyne coupling reaction, the problem of insufficient energy storage performance of existing graphyyne materials is solved, and efficient electrochemical energy storage effect is achieved, and the operation is simple and the material structure is stable.
Patent Information
- Application Number
- CN202310601754.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-25
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-05-25
AI Technical Summary
The existing graphyyne materials have shortcomings in energy storage performance, and the operating conditions of the preparation method are harsh, resulting in unstable material structure and disordered nitrogen distribution.
Graphite alkyne materials are prepared by bottom-up methods, and graphite alkyne-like materials with multi-active sites are formed by synthesizing hexazanaphthalene structural monomers and undergoing alkyne-like coupling reaction under copper catalysis to accurately dopant nitrogen atoms.
The prepared graphiteyne material (HATN-GDY) has excellent electrochemical energy storage properties, which significantly improves the energy storage effect of lithium-ion batteries. It has simple operation, mild reaction and clear material structure.
Smart Images

Figure CN116854078B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon materials, and in particular to a graphyne material, a preparation method and application thereof, and a lithium ion battery. Background Art
[0002] GDY is composed of sp and sp 2 The acetylene bonds and benzene rings form a two-dimensional planar structure of graphdiyne molecules. The two-dimensional graphdiyne molecules are stacked to form a layered structure through van der Waals forces and π-π interactions. The large triangular ring composed of 18-21 carbon atoms forms a three-dimensional pore structure in the layered structure. The plane sp and sp 2 Hybridization makes graphyne highly π-conjugated, uniformly dispersed pore structure and adjustable electronic structure characteristics, showing unique photoelectrochemical and energy storage properties, and has great application potential in energy, catalysis, electronics and other fields. Due to the difference in electronegativity between carbon and nitrogen atoms, the doping of nitrogen atoms can not only improve the surface chemical properties to make it more active, but also adjust its electronic structure. Therefore, nitrogen doping can effectively improve the electrochemical activity of graphyne.
[0003] Current research has found that there are two methods for preparing nitrogen co-doped graphyne: one is a "top-down" method, for example, CN109772413A obtains a nitrogen-doped graphyne material through a high-temperature calcination strategy, but this method has harsh operating conditions, and high temperature will cause the graphyne edge structure to be unstable and the nitrogen element to be distributed disorderly on the graphyne material; the other is a "bottom-up" method, for example, CN111689486A and CN114604848A use nitrogen-containing six-membered ring compounds as raw materials to prepare a series of graphyne materials with orderly nitrogen element distribution.
[0004] However, the graphyne materials disclosed in the prior art have deficiencies in energy storage performance.
[0005] Therefore, there is an urgent need to develop a graphyne material with better energy storage performance. Summary of the invention
[0006] The purpose of the present invention is to overcome the problem of insufficient energy storage performance of graphyne materials in the prior art, and to provide a graphyne material and a preparation method and application thereof, and a lithium ion battery.
[0007] In order to achieve the above object, the first aspect of the present invention provides a graphyne material, wherein the graphyne material comprises a structural unit represented by formula (1):
[0008]
[0009] A second aspect of the present invention provides a method for preparing the graphyne material according to the first aspect, comprising the following steps:
[0010] a) in the presence of a first solvent, reacting 4,6-dibromo-o-phenylenediamine with cyclohexanehexanone to obtain an intermediate product 1;
[0011] b) in the presence of a first catalyst and a second solvent, subjecting the intermediate product 1 to a second reaction with an acetylation agent to obtain an intermediate product 2;
[0012] c) dissolving the intermediate product 2 in a third solvent and performing a third reaction with a deprotection reagent to obtain an intermediate product M;
[0013] d) in the presence of a fourth solvent and a copper material, subjecting the intermediate product M to a coupling reaction to obtain the graphyne material.
[0014] The third aspect of the present invention provides a graphyne material prepared according to the preparation method described in the second aspect.
[0015] The fourth aspect of the present invention provides the use of the graphyne material described in the first and third aspects in the preparation of lithium-ion batteries.
[0016] A fifth aspect of the present invention provides a lithium-ion battery comprising the graphyne material described in the first and third aspects.
[0017] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0018] (1) The graphyne material (HATN-GDY) provided by the present invention has multiple active sites. The structural module of hexaazine has abundant redox active C=N groups, which synergizes with abundant diacetylene units, so that the graphyne material has excellent electrochemical energy storage properties.
[0019] (2) The present invention adopts a bottom-up strategy to prepare graphene material (HATN-GDY). First, the hexaazanaphthalene (HATN) structural monomer is synthesized, and then the graphene material with precise nitrogen atom doping and clear hybrid morphology is prepared through alkynylene coupling reaction.
[0020] (3) The graphyne material (HATN-GDY) prepared by the present invention is an excellent lithium-ion battery electrode material, showing extraordinary energy storage effect, which significantly promotes the application of graphyne material in the field of electrochemical energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a reaction synthesis route diagram of the graphyne material described in the present invention.
[0022] Figure 2 is the hydrogen nuclear magnetic resonance spectrum of the intermediate product 1 of Example 1 of the present invention ( 1 1H NMR).
[0023] Figure 3 The nuclear magnetic resonance hydrogen spectrum of the intermediate product 2 of Example 1 of the present invention is ( 1 1H NMR).
[0024] Figure 4 The nuclear magnetic resonance hydrogen spectrum of the intermediate product 2 of Example 1 of the present invention is ( 13 C NMR).
[0025] Figure 5 This is a transmission electron microscope (TEM) image of the graphyne material prepared in Example 1 of the present invention.
[0026] Figure 6 This is the energy dispersive X-ray spectroscopy elemental mapping (EDS) of the graphyne material prepared in Example 1 of the present invention.
[0027] Figure 7 This is the Raman spectrum of the graphyne material prepared in Example 1 of the present invention.
[0028] Figure 8 This is the infrared spectrum (FTIR) of the graphyne material prepared in Example 1 of the present invention.
[0029] Fig. 9 This is the X-ray photoelectron spectrum (XPS) of the graphyne material prepared in Example 1 of the present invention.
[0030] Fig.10 This is the ultraviolet spectrum (UV-vis) of the graphyne material prepared in Example 1 of the present invention.
[0031] Fig.11 This is the IV curve of the graphyne material prepared in Example 1 of the present invention.
[0032] Fig.12 The cycle performance diagram (a) and rate performance diagram (b) of using the graphyne material prepared in Example 1 of the present invention for the negative electrode of a lithium ion battery are shown.
[0033] Fig.13 The cycle performance diagram (a) and rate performance diagram (b) of using the graphyne material prepared in Example 2 of the present invention for the negative electrode of a lithium ion battery are shown.
[0034] Fig.14 The cycle performance diagram (a) and rate performance diagram (b) of using the graphyne material prepared in Example 3 of the present invention for the negative electrode of a lithium ion battery are shown. DETAILED DESCRIPTION
[0035] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0036] A first aspect of the present invention provides a graphyne material, wherein the graphyne material comprises a structural unit represented by formula (1):
[0037]
[0038] The nitrogen-rich graphyne material (HATN-GDY) with multiple active sites provided in the present invention has a uniform structural unit, and the molar ratio of C:N=6:1 is precisely controlled in the graphyne as a whole and in the structural unit. The nitrogen-rich graphyne with multiple active sites of the present invention has precise nitrogen atom doping, abundant redox active C=N groups and diacetylene units, has excellent electrochemical energy storage properties, and exhibits extraordinary energy storage effects when used as a lithium ion battery electrode material.
[0039] In the present invention, the molecular formula of the Graphene material can be expressed as (C 36 H6N6) n .
[0040] In some embodiments of the present invention, the graphyne material includes n structural units represented by formula (1), wherein n is any integer greater than 6, such as 6, 7, 8, 9, 10, 15, 20, 30, preferably any integer greater than 16.
[0041] In some embodiments of the present invention, the structural formula of the graphyne material is as shown in formula (2):
[0042]
[0043] In some embodiments of the present invention, the bandgap of the Graphene material is 2.08-2.12 eV, and the conductivity is 3.5×10 -4 -4×10 -4 sm -1 .
[0044] In the present invention, the bandgap width can be obtained from the ultraviolet spectrum.
[0045] In the present invention, the test method of conductivity is as follows: a device is manufactured using a Cu / HATN-GDY / Cu structure, and conductivity is measured at a bias voltage of -4V to 4V. The conductivity is calculated by the equation ρ=RS / L, where ρ is conductivity, R is resistance, S is electrode area, and L is HATN-GDY thickness.
[0046] The second aspect of the present invention provides a method for preparing the graphyne material according to the first aspect, comprising the following steps:
[0047] a) in the presence of a first solvent, reacting 4,6-dibromo-o-phenylenediamine with cyclohexanehexanone to obtain an intermediate product 1;
[0048] b) in the presence of a first catalyst and a second solvent, subjecting the intermediate product 1 to a second reaction with an acetylation agent to obtain an intermediate product 2;
[0049] c) dissolving the intermediate product 2 in a third solvent and performing a third reaction with a deprotection reagent to obtain an intermediate product M;
[0050] d) in the presence of a fourth solvent and a copper material, subjecting the intermediate product M to a coupling reaction to obtain the graphyne material.
[0051] The present invention prepares the graphyne by subjecting synthesized hexynyl hexaazinaphthalene monomers to a coupling reaction under the catalysis of copper. The preparation method of the present invention has the characteristics of simple operation and mild reaction, and can obtain nitrogen-rich graphyne with multiple active sites and a clear structure.
[0052] The reaction product (in solution form) of each step is filtered, washed with water, and washed with alcohol (such as ethanol) to obtain the product of each step.
[0053] The reaction synthesis route of the Graphene material of the present invention is as follows: Figure 1 shown.
[0054] The deprotecting agent functions to remove the silicon protecting group of the terminal alkyne.
[0055] In some embodiments of the present invention, the steps a), b), c) and d) are performed under the protection of a protective gas.
[0056] In some embodiments of the present invention, the protective gas is selected from at least one of nitrogen, helium and argon.
[0057] In some embodiments of the present invention, in step a), the molar ratio of 4,6-dibromo-o-phenylenediamine to cyclohexanone is 0.5-3:3-10, preferably 1-2:4-8.
[0058] In some embodiments of the present invention, the ratio of 4,6-dibromo-o-phenylenediamine to the first solvent is 4-8 mmol:150-250 mL, that is, the amount of the first solvent used is 150-250 mL relative to 4-8 mmol of 4,6-dibromo-o-phenylenediamine.
[0059] In some embodiments of the present invention, the first solvent is an acidic organic solvent.
[0060] In some embodiments of the present invention, the acidic organic solvent is selected from at least one of acetic acid, propionic acid and octanoic acid.
[0061] In some embodiments of the present invention, the first reaction is carried out under reflux conditions. In the present invention, the first reaction is carried out under reflux conditions to ensure sufficient reaction.
[0062] In some embodiments of the present invention, the conditions of the first reaction include: a temperature of 120-160°C, for example, 120°C, 130°C, 140°C, 150°C, 160°C, and any value within the range composed of any two of the above values, preferably 130-150°C; a time of 20-80h, for example, 20h, 30h, 40h, 50h, 60h, 70h, 80h, and any value within the range composed of any two of the above values, preferably 24-72h.
[0063] In some embodiments of the present invention, in step b), the molar ratio of the intermediate product 1, the first catalyst and the acetylation agent is 0.5-3:0.02-0.2:5-15, preferably 1-2:0.03-0.15:6-12.
[0064] In some embodiments of the present invention, the ratio between the intermediate product 1 and the second solvent is 2-4 mmol: 25-100 mL, that is, relative to 2-4 mmol of the intermediate product 1, the amount of the second solvent used is 25-100 mL.
[0065] In some embodiments of the present invention, the first catalyst is a complex of Pd(PPh3)4 and CuI or a complex of PdCl2(PPh3)2 and CuI, preferably a complex of PdCl2(PPh3)2 and CuI, wherein the molar ratio of PdCl2(PPh3)2 and CuI is 1-5:2-10.
[0066] In some embodiments of the present invention, the second solvent is a basic organic solvent.
[0067] In some embodiments of the present invention, the alkaline organic solvent is selected from at least one of triethylamine, diisopropylamine and pyridine.
[0068] In some embodiments of the present invention, the acetylation agent is selected from at least one of trimethylethynylsilane and triisopropylethynylsilane.
[0069] In some embodiments of the present invention, the second reaction is carried out under closed conditions.
[0070] In some embodiments of the present invention, the conditions of the second reaction include: a temperature of 90-130°C, for example, 90°C, 100°C, 110°C, 120°C, 130°C, and any value within the range composed of any two of the above values, preferably 100-120°C; a time of 20-52h, for example, 20h, 25h, 30h, 35h, 40h, 45h, 50h, 52h, and any value within the range composed of any two of the above values, preferably 24-48h.
[0071] In some embodiments of the present invention, in step c), the molar ratio of the intermediate product 2 to the deprotection agent is 0.5-5:5-20, preferably 1-3:6-18.
[0072] In some embodiments of the present invention, the third solvent is selected from at least one of tetrahydrofuran, dichloromethane and chloroform.
[0073] In some embodiments of the present invention, the deprotection agent is selected from at least one of tetrabutylammonium fluoride, potassium carbonate and potassium hydroxide, preferably tetrabutylammonium fluoride (TBAF).
[0074] In some embodiments of the present invention, the conditions of the third reaction include: temperature of -10-10°C, for example, -10°C, -5°C, 0°C, 5°C, 10°C, and any value within the range composed of any two of the above values, preferably 0-5°C; time of 0.2-1.2h, for example, 0.2h, 0.5h, 0.8h, 1h, 1.2h, and any value within the range composed of any two of the above values, preferably 0.3-1h.
[0075] In some embodiments of the present invention, in step d), the intermediate product M is dissolved in a fourth solvent to form an M solution, the M solution is dropped into a solution containing a copper material to perform a coupling reaction, and the reaction product is treated to obtain the graphyne material.
[0076] In some embodiments of the present invention, the concentration of the intermediate product M in the M solution is 0.03-0.1 mM.
[0077] In some embodiments of the present invention, the volume ratio of the M solution to the solution containing the copper material is 1-3:2-6.
[0078] In some embodiments of the present invention, the fourth solvent is selected from at least one of pyridine and tetramethylethylenediamine.
[0079] In some embodiments of the present invention, the copper material is selected from at least one of copper sheet, copper foam and cuprous iodide.
[0080] In some embodiments of the present invention, the conditions of the coupling reaction include: a temperature of 60-120°C, for example 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, and any value within the range composed of any two of the above values, preferably 80-110°C; a time of 1.5-5 days, for example 1.5 days, 2 days, 3 days, 4 days, 5 days, and any value within the range composed of any two of the above values, preferably 2-4 days.
[0081] According to a particularly preferred embodiment of the present invention, a method for preparing a graphyne material comprises the following steps:
[0082] a) Under nitrogen protection, 4,6-dibromo-o-phenylenediamine and cyclohexanone are reacted in acetic acid to obtain intermediate product 1:
[0083]
[0084] b) Under nitrogen protection, using a complex of PdCl2(PPh3)2 and CuI as a catalyst, the intermediate product 1 was reacted with triisopropylethynylsilane in triethylamine to obtain the intermediate product 2:
[0085]
[0086] c) Under nitrogen protection, the intermediate product 2 is reacted with tetrabutylammonium fluoride in tetrahydrofuran to obtain the intermediate product M:
[0087]
[0088] d) dissolving the intermediate product M in pyridine to form a solution, dropping the solution into a pyridine solution containing a copper sheet to carry out a coupling reaction, and treating the reaction product to obtain the graphene material (HATN-GDY):
[0089]
[0090] The third aspect of the present invention provides a graphyne material prepared according to the preparation method described in the second aspect.
[0091] The fourth aspect of the present invention provides the use of the graphyne material described in the first and third aspects in the preparation of lithium-ion batteries.
[0092] A fifth aspect of the present invention provides a lithium-ion battery comprising the graphyne material described in the first and third aspects.
[0093] Using the graphyne material prepared by the present invention as an electrode material for a lithium ion battery can give the lithium ion battery excellent energy storage performance.
[0094] The present invention will be described in detail below through examples.
[0095] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.
[0096] Example 1
[0097] This example is used to illustrate the preparation of Graphdine material.
[0098] a) Under nitrogen protection, 5 mmol of 4,6-dibromo-o-phenylenediamine and 20 mmol of cyclohexanone octahydrate were refluxed in 200 mL of acetic acid at 140° C. for 50 h, and the intermediate product 1 was obtained after treatment, namely hexabromohexaazanaphthalene;
[0099] b) Under nitrogen protection, 3 mmol of intermediate product 1, 0.05 mmol of PdCl2(PPh3)2, and 0.1 mmol of CuI were dissolved in 60 mL of triethylamine, and 20 mmol of triisopropylethynylsilane was added. The mixture was reacted at 110° C. for 30 h in a sealed container, and the intermediate product 2 was obtained after treatment, namely bis(triisopropylsilylethynyl)hexaazanaphthalene;
[0100] c) Under nitrogen protection, 0.2 mmol of the intermediate product 2 was dissolved in 40 mL of THF, 1 mL of a 1.0 M TBAF tetrahydrofuran solution was added, and the mixture was reacted at 0° C. for 0.5 h. After treatment, the intermediate product M was obtained, which was hexynylhexaazanaphthalene;
[0101] d) The intermediate product M was dissolved in 50 mL of pyridine solution to form a solution with a concentration of 0.05 mM, and the solution was dropped into 100 mL of pyridine solution containing a copper sheet, and reacted at 100° C. for 3 days to obtain a graphyne material after treatment.
[0102] Figure 2 This is the H NMR spectrum of intermediate 1 ( 1 HNMR), 400MHz, DMSO, TMS: δ = (s = 8.50Hz, 6H).
[0103] Figure 3 is the H NMR spectrum of intermediate 2 ( 1HNMR), 400MHz, CDCl3, TMS: δ = 8.84 (s, J = 8.84Hz, 6H), 1.21 (s, J = 1.21, 126H).
[0104] Figure 4 is the H NMR spectrum of intermediate 2 ( 13 C NMR), 100MHz, CDCl3: δ = 143.96, 142.71, 135.54, 128.97, 104.29, 100.81, 18.78, 11.32ppm.
[0105] Figure 5 This is a transmission electron microscope (TEM) image of the graphyne material prepared in Example 1. Under different magnification conditions of 500nm and 100nm, it is observed that the graphyne material presents a large-scale thin film with a uniform and continuous structure.
[0106] Figure 6 This is an energy dispersive X-ray spectroscopy element mapping (EDS) diagram of the graphyne material prepared in Example 1. It can be seen from the diagram that carbon and nitrogen are evenly distributed.
[0107] Figure 7 This is the Raman spectrum of the graphyne material prepared in Example 1. It can be seen that 1096 cm -1 , 1341cm -1 , 1496cm -1 , 1564cm -1 , 2201cm -1 There are five main peaks, including 2201cm -1 It is the stretching vibration peak of diyne, which proves that the acetylene-acetylene coupling reaction occurs and the graphyne is successfully synthesized.
[0108] Figure 8 This is the infrared spectrum (FTIR) of the graphyne material prepared in Example 1. It can be seen that the fingerprint peak of the aromatic heterocycle is 800-1600cm -1 , and 2850-3000cm -1 There is no stretching vibration peak of terminal alkyne CH, indicating that a coupling reaction has occurred in the monomer.
[0109] Fig. 9 This is the X-ray photoelectron spectrum (XPS) of the graphyne material prepared in Example 1. It can be seen from the figure that the graphyne material is mainly composed of C and N elements, and there is a characteristic peak of the N element at 398.6 eV and a characteristic peak of the C element at 284.6 eV.
[0110] Fig.10This is the ultraviolet spectrum (UV-vis) of the graphyne material prepared in Example 1. It is calculated that the band gap width of the graphyne material is about 2.10 eV, which has a relatively small band gap width.
[0111] Fig.11 This is the IV curve of the graphyne material prepared in Example 1. It can be seen that the conductivity of the graphyne material is 3.75×10 -4 S m -1 .
[0112] Example 2
[0113] This example is used to illustrate the preparation of Graphdine material.
[0114] a) Under nitrogen protection, 8 mmol of 4,6-dibromo-o-phenylenediamine and 16 mmol of cyclohexanone octahydrate were dissolved in 150 mL of acetic acid and refluxed at 130° C. for 24 h. After treatment, the intermediate product 1 was obtained, which was hexabromohexaazanaphthalene;
[0115] b) Under nitrogen protection, 2 mmol of intermediate product 1, 0.02 mmol of PdCl2(PPh3)2, and 0.04 mmol of CuI were dissolved in 25 mL of triethylamine, 12 mmol of triisopropylethynylsilane was added, and the mixture was reacted at 100° C. for 24 h in a sealed container. After treatment, intermediate product 2 was obtained, namely bis(triisopropylsilylethynyl)hexaazinapthane;
[0116] c) Under nitrogen protection, 0.1 mmol of the intermediate product 2 was dissolved in 20 mL of THF, and 0.6 mL of a 1.0 M tetrahydrofuran solution of TBAF was added, and the mixture was reacted at 5° C. for 0.3 h. After treatment, the intermediate product M was obtained, which was hexynylhexaazanaphthalene;
[0117] d) The intermediate product M was dissolved in 25 mL of pyridine solution to form a solution with a concentration of 0.03 mM, and then dropped into 50 mL of pyridine solution containing a copper sheet, and reacted at 110° C. for 2 days to obtain a graphyne material after treatment.
[0118] Example 3
[0119] This example is used to illustrate the preparation of Graphdine material.
[0120] a) Under nitrogen protection, 4 mmol of 4,6-dibromo-o-phenylenediamine and 32 mmol of cyclohexanehexaketone octahydrate were refluxed at 150° C. for 72 h in 250 mL of acetic acid, and the intermediate product 1 was obtained after treatment, namely hexabromohexaazanaphthalene;
[0121] b) Under nitrogen protection, 4 mmol of intermediate product 1, 0.10 mmol of PdCl2(PPh3)2, and 0.20 mmol of CuI were dissolved in 25 mL of triethylamine, and 24 mmol of triisopropylethynylsilane was added. The mixture was reacted at 120° C. for 48 h in a sealed container, and the intermediate product 2 was obtained after treatment, namely bis(triisopropylsilylethynyl)hexaazanaphthalene;
[0122] c) Under nitrogen protection, 0.3 mmol of the intermediate product 2 was dissolved in 60 mL of THF, and 1.8 mL of a 1.0 M TBAF tetrahydrofuran solution was added, and the mixture was reacted at 3° C. for 1 h. After treatment, the intermediate product M was obtained, which was hexynylhexaazanaphthalene;
[0123] d) The intermediate product M was dissolved in 75 mL of pyridine solution to form a solution with a concentration of 0.1 mM, and then dropped into 150 mL of pyridine solution containing a copper sheet, and reacted at 80° C. for 4 days to obtain a graphyne material after treatment.
[0124] Example 4
[0125] This example is used to illustrate the preparation of Graphdine material.
[0126] a) Under nitrogen protection, 2 mmol of 4,6-dibromo-o-phenylenediamine and 12 mmol of cyclohexanone octahydrate were dissolved in 250 mL of acetic acid and refluxed at 120° C. for 20 h. After treatment, the intermediate product 1 was obtained, which was hexabromohexaazanaphthalene;
[0127] b) Under nitrogen protection, 1 mmol of intermediate product 1, 0.10 mmol of PdCl2(PPh3)2, and 0.20 mmol of CuI were dissolved in 25 mL of triethylamine, 6 mmol of triisopropylethynylsilane was added, and the mixture was reacted at 130° C. for 52 h in a sealed container. After treatment, intermediate product 2 was obtained, namely bis(triisopropylsilylethynyl)hexaazanaphthalene;
[0128] c) Under nitrogen protection, 0.5 mmol of the intermediate product 2 was dissolved in 60 mL of THF, 1.8 mL of a 1.0 M TBAF tetrahydrofuran solution was added, and the mixture was reacted at -10°C for 1.2 h. After treatment, the intermediate product M was obtained, which was hexynylhexaazanaphthalene;
[0129] d) The intermediate product M was dissolved in 75 mL of pyridine solution to form a solution with a concentration of 0.08 mM, and the solution was dropped into 150 mL of pyridine solution containing a copper sheet, and reacted at 60° C. for 5 days to obtain a graphyne material after treatment.
[0130] Example 5
[0131] This example is used to illustrate the preparation of Graphdine material.
[0132] a) Under nitrogen protection, 6 mmol of 4,6-dibromo-o-phenylenediamine and 6 mmol of cyclohexanone octahydrate were dissolved in 150 mL of acetic acid and refluxed at 120° C. for 20 h. After treatment, the intermediate product 1 was obtained, which was hexabromohexaazanaphthalene;
[0133] b) Under nitrogen protection, 6 mmol of intermediate product 1, 0.10 mmol of PdCl2(PPh3)2, and 0.20 mmol of CuI were dissolved in 25 mL of triethylamine, 30 mmol of triisopropylethynylsilane was added, and the mixture was reacted at 90° C. for 20 h in a sealed container. After treatment, intermediate product 2 was obtained, namely bis(triisopropylsilylethynyl)hexaazanaphthalene;
[0134] c) Under nitrogen protection, 5 mmol of the intermediate product 2 was dissolved in 60 mL of THF, 10 mL of a 1.0 M TBAF tetrahydrofuran solution was added, and the mixture was reacted at 10° C. for 0.2 h. After treatment, the intermediate product M was obtained, which was hexynylhexaazanaphthalene;
[0135] d) The intermediate product M was dissolved in 75 mL of pyridine solution to form a solution with a concentration of 0.07 mM, and the solution was dropped into 150 mL of pyridine solution containing a copper sheet, and reacted at 120° C. for 1.5 days to obtain a graphyne material after treatment.
[0136] Comparative Example 1
[0137] The graphene material H1F1-GDY developed by Tiantian Lu et al. (Tiantian Lu et al. Adjusting the interface structure of graphdiyne by H and F co-doping for enhanced capacity and stability in Li-ion battery, Energy Storage Materials 29 (2020) 131–139) was used as comparison example 1.
[0138] Comparative Example 2
[0139] A polymer (NSHATN) containing a HATN structure developed by Jinquan Wang et al. (Jinquan Wang, et al. A nanoporous sulfur-bridged hexaazatrinaphthylene framework as an organic cathode for lithium ion batteries with well-balanced electrochemical performance, Chem. Commun., 2018, 54, 7681) is used as Comparative Example 2.
[0140] Test Case
[0141] The Graphene material prepared in Examples 1-3 was dried in a vacuum oven at 120°C for 10 h and then used as an electrode without adding any binder. Pure Li foil was used as a counter electrode, separated from the working electrode by a Celgard 2500 polymer separator. The electrolyte solution was ethylene carbonate (EC) / dimethyl carbonate (DMC) / diethyl carbonate (DEC) (volume ratio of 1:1:1), 1M LiPF6, and 5% by volume of vinylene carbonate (VC) as an additive.
[0142] Cyclic performance test: at 50mA g -1 At a current density of 2.5V, the LAND battery test system was used to perform 200 cycle tests in the range of 0.05V and 3V to obtain the average coulombic efficiency and capacity retention rate, as shown in Figure 2. Fig.12 (a)-14(a).
[0143] Rate performance test: LAND battery test system was used to test in the range of 0.05V and 3V, respectively at 50mAg -1 , 100mA g -1 , 200mA g -1 , 500mA g -1 , 1000mA g -1 , 2000mA g -1 , 5000mA g -1 , 50mA g -1 After 5 cycles, the battery capacity data at different current densities are obtained, such as Fig.12 (b)-14(b).
[0144] The results are shown in Table 1.
[0145] Table 1
[0146]
[0147]
[0148] It can be seen from the results in Table 1 that the Graphdiyne material (HATN-GDY) with multiple active sites provided by the present invention as an electrode has a high conductivity at 50 mA g -1 At a current of 2063 mA hg -1 The above indicates that the electrode has excellent rate performance. Among them, the specific capacity of Examples 1-3 of the present invention is 6 times higher than that of Comparative Example 2.
[0149] In addition, the Graphdine material (HATN-GDY) with multiple active sites provided by the present invention is used as an electrode at 50 mAg -1 At a current density of , the specific capacity is still maintained above 89.4% after 200 cycles, the capacity retention rate is high, and the average coulombic efficiency is also better than that of comparative example 1.
[0150] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A graphyne material, characterized in that: The graphyne material comprises a structural unit shown in formula (1): 。 2. The graphyne material according to claim 1, wherein: The graphyne material comprises n structural units represented by formula (1), wherein n is any integer greater than 6.
3. The graphyne material according to claim 2, wherein: n is any integer greater than or equal to 16.
4. The graphyne material according to claim 1 or 2, wherein: The band gap of the Graphene material is 2.08-2.12 eV and the conductivity is 3.5×10 -4 -4×10 -4 sm -1 .
5. A method for preparing a graphyne material according to any one of claims 1 to 4, characterized in that: The steps include: a) in the presence of a first solvent, reacting 4,6-dibromo-o-phenylenediamine with cyclohexanone to obtain an intermediate product 1; b) in the presence of a first catalyst and a second solvent, subjecting the intermediate product 1 to a second reaction with an acetylation agent to obtain an intermediate product 2; c) dissolving the intermediate product 2 in a third solvent and reacting it with a deprotecting agent to obtain an intermediate product M; d) in the presence of a fourth solvent and a copper material, subjecting the intermediate product M to a coupling reaction to obtain the graphyne material; Wherein, the first catalyst is a complex of Pd(PPh3)4 and CuI or a complex of PdCl2(PPh3)2 and CuI; The acetylenylating agent is selected from at least one of trimethylethynylsilane and triisopropylethynylsilane; The deprotection agent is selected from at least one of tetrabutylammonium fluoride, potassium carbonate and potassium hydroxide.
6. The preparation method according to claim 5, wherein: The steps a), b), c) and d) are carried out under the protection of protective gas.
7. The preparation method according to claim 6, wherein: The protective gas is selected from at least one of nitrogen, helium and argon.
8. The preparation method according to claim 5, wherein: In step a), the molar ratio of 4,6-dibromo-o-phenylenediamine to cyclohexanone is 0.5-3:3-10; and / or, the ratio between 4,6-dibromo-o-phenylenediamine and the first solvent is 4-8 mmol:150-250 mL; and / or, the first solvent is an acidic organic solvent; and / or, the first reaction is carried out under reflux conditions; And / or, the conditions of the first reaction include: temperature of 120-160° C.; time of 20-80 h.
9. The preparation method according to claim 8, wherein: In step a), the molar ratio of 4,6-dibromo-o-phenylenediamine to cyclohexanehexanone is 1-2:4-8; And / or, the acidic organic solvent is selected from at least one of acetic acid, propionic acid and octanoic acid; And / or, the conditions of the first reaction include: temperature of 130-150° C.; time of 24-72 h.
10. The preparation method according to claim 5, wherein: In step b), the molar ratio of the intermediate product 1, the first catalyst and the acetylation agent is 0.5-3:0.02-0.2:5-15; and / or, the ratio between the intermediate product 1 and the second solvent is 2-4 mmol:25-100 mL; And / or, the first catalyst is a complex of PdCl2(PPh3)2 and CuI, wherein the molar ratio of PdCl2(PPh3)2 to CuI is 1-5:2-10; and / or, the second solvent is an alkaline organic solvent; And / or, the second reaction is carried out under closed conditions; And / or, the conditions of the second reaction include: temperature of 90-130° C.; time of 20-52 h.
11. The preparation method according to claim 10, wherein: In step b), the molar ratio of the intermediate product 1, the first catalyst and the acetylation agent is 1-2:0.03-0.15:6-12; and / or, the alkaline organic solvent is selected from at least one of triethylamine, diisopropylamine and pyridine; And / or, the conditions of the second reaction include: temperature of 100-120° C.; time of 24-48 h.
12. The preparation method according to claim 5, wherein: In step c), the molar ratio of the intermediate product 2 to the deprotection reagent is 0.5-5:5-20; And / or, the third solvent is selected from at least one of tetrahydrofuran, dichloromethane and chloroform; And / or, the conditions of the third reaction include: temperature of -10-10°C; time of 0.2-1.2 h.
13. The preparation method according to claim 12, wherein: In step c), the molar ratio of the intermediate 2 to the deprotection reagent is 1-3:6-18; And / or, the conditions of the third reaction include: temperature of 0-5°C; time of 0.3-1 h.
14. The preparation method according to claim 5, wherein: In step d), the intermediate product M is dissolved in a fourth solvent to form an M solution, the M solution is dropped into a copper material solution to perform a coupling reaction, and the reaction product is treated to obtain the graphyne material; and / or, the fourth solvent is selected from at least one of pyridine and tetramethylethylenediamine; And / or, the copper material is selected from at least one of copper sheet, copper foam and cuprous iodide; And / or, the conditions of the coupling reaction include: a temperature of 60-120°C; The time is 1.5-5 days.
15. The preparation method according to claim 14, wherein: The concentration of the intermediate product M in the M solution is 0.03-0.1 mM; And / or, the volume ratio of the M solution to the copper material solution is 1-3:2-6; And / or, the coupling reaction conditions include: temperature of 80-110° C.; time of 2-4 days.
16. A graphyne material obtained according to the preparation method according to any one of claims 5 to 15.
17. Use of the graphyne material according to any one of claims 1 to 4 and 16 in the preparation of lithium-ion batteries.
18. A lithium ion battery comprising the graphyne material according to any one of claims 1 to 4 and 16.
Citation Information
Patent Citations
Nitrogen- and sulfur-codoped graphdiyne material, preparation method and application thereof, and oxygen evolution reaction catalyst containing same
CN109772413A
Nitrogen-rich graphdiyne and preparation method thereof
CN114604848A
Novel triazine carbon-rich two-dimensional material and preparation method thereof
CN107098910A
Preparation method of N-containing graphdiyne material
CN111689486A